Rancang Bangun Media Praktikum Mata Kuliah Sistem Operasi Dengan Kernel Virtual Machine Server Terintegrasi Dengan Sistem Akademik - Egi Adithia Pradana; Anisah Amelia Putry; Selvi Mursidayanti (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Virtualization is a necessity that every company cannot resist anymore, not only large-scale, but also medium and small. This research aims to develop a KVM-based server virtualization platform as a means of replacing desktop-based virtualization applications which are classified as full virtualization types, there are many limitations. Based on the results of the research and discussion above, it can be concluded that the Operating System as one of the courses taught from the field of computer science can still be supported technically deeper in terms of implementing practicum or courses taught in the campus laboratory area, with this research it is hoped that this server kvm system can be a solution for students and lecturers because it can be accessed freely without having to bump into shortcomings Lab computer specifications and can also be accessed directly by using student computer devices, such as laptops and even tablets both based on Android and IOS. With a centralized system on the server, students and lecturers can access the virtual server simply with npm and password that has been created, no need to repeat from scratch if their virtual machine is deleted or moved computers.